Role of fibroblast growth factor-23 as an early marker of metabolic bone disease of prematurity - Sandra Llorente-Pelayo; Pablo Docio; Silvia Arriola; Bernardo A. Lavín-Gómez; María T. García-Unzueta; María Ángeles Ballesteros; María J. Cabero-Pérez; Domingo González-Lamuño (BMC, 2024)
Abstract Purpose Metabolic bone disease of prematurity (MBDP) remains a significant cause of morbidity in extremely premature newborns. In high-risk patients, suspected diagnosis and subsequent treatment modifications, with limitations in terms of sensitivity and specificity, rely on low phosphorus levels and/or high levels of alkaline phosphatase (ALP). We investigated the potential of fibroblast growth factor-23 (FGF23) as an early marker for MBDP when measured at 3-4 weeks of life in at-risk patients. Methods A single-center prospective observational non-interventional study including preterm newborns of both sexes, with a gestational age of less than 32 weeks and/or a birth weight of less than 1500 g. In the standard biochemical screening for MBDP performed between 3 and 4 weeks of life within a nutritional profile, the determination of FGF23 was included along with other clinical and metabolic studies. The study was conducted at Marqués de Valdecilla University Hospital in Santander, Spain, from April 2020 to March 2021. Participants provided informed consent. Biochemical analyses were conducted using various platforms, and follow-up evaluations were performed at the discretion of neonatologists. Patients at high risk for MBDP received modifications in treatment accordingly. The sample was descriptively analyzed, presenting measures of central tendency and dispersion for continuous variables, and absolute numbers/percentages for categorical ones. Tests used included t-tests, Mann‒Whitney U tests, chi-square tests, logistic regressions, Pearson correlation, and ROC curve analysis (IBM SPSS Statistics version 19). Significance level: P < 0.05. Results In the study involving 25 at-risk premature newborns, it was found that 20% (n = 5) were diagnosed with MBDP. Three of these patients (60%) were identified as high-risk based on standard biochemical evaluation at 3-4 weeks of age, while the other two patients (40%) were diagnosed in subsequent weeks. However, in all 5 patients, measurement of FGF23 levels would allow for early identification and optimization of treatment before other markers become altered. Low levels of FGF23 at 3-4 weeks, even with normal phosphorus and ALP levels, indicate the need for modifications in nutritional supplementation. Conclusions MBDP remains a significant concern in extremely premature newborns. Current diagnostic methods rely on limited biochemical markers. Early detection of low FGF23 levels enables timely interventions, potentially averting demineralization.